Microstructure of organometallic derived PLZT ceramics - Stojanovic, B. D.; Foschini, C. R.; Zaghete, M. A.; Cilense, M.; Cavalheiro, A. A.; Paiva-Santos, C. O.; Varela, José Arana [UNESP] (Elsevier B.V., 2001)
The PLZT powders with the formula Pb0.905La0.095(Zr0.65Ti0.35)(0.976)O-3+3.5 wt.% PbO were prepared by the organometallic precursor method (Pechini and partial oxalate processes). The microstructure of sintered 9.5/65/35 PLZT ceramics obtained from a partial oxalate procedure shows that the outstanding feature of this microstructure is its fairly uniform grains of about 1.8 mum. The microstructure of sintered PLZT ceramics obtained by the Pechini process consists of uniform small randomly- oriented grains tightly bonded together in the central part of the sample with,a grain size of about 1.2 mum. Cubic and elongated grains are formed at the sample's border. The microstructures of hot pressed PLZT ceramics obtained from both processes are dense and rather uniform. After a double stage of hot pressing (2 plus 20 h) the microstructure of PLZT is fully dense, uniform and homogeneous with a grain size of approximately 2.5 mum. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: hot-pressing; microstructure-final; PLZT; precursors; organic